ANALISIS KELAYAKAN INVESTASI USAHA KECIL WARNET (Studi Pada Warnet Bulian City Net Muara Bulian) - Sumantri Sumantri (Universitas Batanghari Jambi, 2018)
Market Prospects At this time the need for information society is greatly improved, to meet this need required adequate facilities in order to send and receive good information, especially in telecommunication services. Warnet as a business that provides computer rental services to access the internet. Because the cafe business around Islamic High School is only 5 (five), then the researchers only do 1 sample. Assessments that have been done above with various methods of business feasibility study analysis then the business cafe